2007
DOI: 10.1111/j.1742-4658.2007.05993.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 activates the atypical Rio1p kinase and promotes its cell‐cycle phase‐dependent degradation in yeast

Abstract: The protein kinase casein kinase 2 (CK2) is ubiquitous in eukaryotes and is responsible for the Ser ⁄ Thr phosphorylation of a large number of protein substrates [1][2][3]. The active holoenzyme is most often a heterotetramer composed of two catalytic a subunits, a (encoded by CKA1) and a¢ (encoded by CKA2), and two regulatory b subunits, b and b¢ in Saccharomyces cerevisiae (CKB1 and CKB2). The enzyme occurs in all possible combinations of a and b subunits [4,5]. In yeast, deletion of the gene for one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
(116 reference statements)
3
24
0
Order By: Relevance
“…The measured kinase activities were identical (Fig. 4b), confirming an earlier report that recombinant Rio1 lacking a similar C-terminal region is still active as a kinase in vitro 22 . To exclude a possible contribution from casein kinases CK1 and CK2, shown to co-purify with full-length Rio1 (refs 12,22) and with Rio1 lacking its C-terminal 46 residues 9 , the assay was repeated in the presence of CK1 and CK2 inhibitors.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The measured kinase activities were identical (Fig. 4b), confirming an earlier report that recombinant Rio1 lacking a similar C-terminal region is still active as a kinase in vitro 22 . To exclude a possible contribution from casein kinases CK1 and CK2, shown to co-purify with full-length Rio1 (refs 12,22) and with Rio1 lacking its C-terminal 46 residues 9 , the assay was repeated in the presence of CK1 and CK2 inhibitors.…”
Section: Resultssupporting
confidence: 89%
“…A previous report indicated that Rio1, overexpressed from the P GAL10 promoter, becomes degraded in S phase, suggesting Rio1 stability is cell cycle regulated 22 . However, our western blot analyses of yeast endogenously expressing Rio1 showed that its protein levels do not change through the cell cycle (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…To date, only two direct substrates of Rio1 in yeast are known: Rio1 itself (16,68,69) and Rpa43; a conserved subunit of RNA polymerase I (16). To identify protein interactors, we tagged Rio1 N- or C-terminally with either the LexA- or the Gal4 DNA-binding domain.…”
Section: Resultsmentioning
confidence: 99%
“…A corollary of this model is that mechanisms exist to alter RioK1 and/or pICln protein levels or change their affinity for PRMT5 and thereby impart spatial and temporal control over substrate specificity of the PRMT5 complex. Indeed, yeast Rio1p is degraded at the G 1 /S transition of the cell cycle in a casein kinase 2 (CK2)-dependent manner (50). This, together with the fact that human RioK1 is a CK2 substrate in vitro 5 suggests that a similar mechanism may control RioK1 protein levels in human cells.…”
Section: Discussionmentioning
confidence: 99%